2022
DOI: 10.3390/inorganics10070097
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Substitution at a Coordinatively Saturated Five-Membered NHC∙Haloborane Centre

Abstract: In this paper, we have used a saturated five-membered N-Heterocyclic carbene (5SIDipp = 1,3-bis-(2,6-diisopropylphenyl)imidazolin-2-ylidine) for the synthesis of SNHC-haloboranes adducts and their further nucleophilic substitutions to put unusual functional groups at the central boron atom. The reaction of 5-SIDipp with RBCl2 yields Lewis-base adducts, 5-SIDipp·RBCl2 [R = H (1), Ph (2)]. The hydrolysis of 1 gives the NHC stabilized boric acid, 5-SIDipp·B(OH)3 (3), selectively. Replacement of chlorine atoms fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…[5][6][7][8][9][10][11] In the same line, Radius and coworkers established carbene•alane/gallane chemistry and its facile halogenation. [12][13][14] Due to our current interest in boron chemistry, [15][16][17][18][19] we proceeded to study the chemistry of 6-SIDipp with boranes. In our previous communication, we have shown that the reaction of a saturated six-membered N-heterocyclic carbene (6-SIDipp) with BH 3 led to the formation of an adduct, 6-SIDipp•BH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] In the same line, Radius and coworkers established carbene•alane/gallane chemistry and its facile halogenation. [12][13][14] Due to our current interest in boron chemistry, [15][16][17][18][19] we proceeded to study the chemistry of 6-SIDipp with boranes. In our previous communication, we have shown that the reaction of a saturated six-membered N-heterocyclic carbene (6-SIDipp) with BH 3 led to the formation of an adduct, 6-SIDipp•BH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to our recent success in saturated N-heterocyclic carbenes, [15][16][17][18] we commenced our study by evaluating the reaction between 5-SIDipp • BH 3 (1) and diphenyldiselenide (PhSeÀ SePh). Monitoring the reaction by 11 B NMR spectroscopy revealed the formation of mixture of both mono and bis selenides (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…§ Complex 6 is a rare example of a heteroleptic, monometallic barium alkoxide. The ring-opening of thf has been previously reported for a number of systems built around oxophilic metals, [25][26][27][28][29][30] frustrated Lewis pairs based on phosphines [31][32][33][34] or NHCc, 48 even middle-to-late transition metals. 49,50 The formation of 6 presumably occurs via nucleophilic attack by the phosphorus atom on the thf α-carbon atom, resulting in ring opening, while the increased negative charge on the now Ba-coordinated oxygen atom also results in borane migration from the phosphine to generate a more stable Lewis adduct.…”
Section: Dalton Transactions Papermentioning
confidence: 79%